Elevation of Symplocos macrophylla subsp. namboodiriana (Symplocaceae) to the species rank - Stephan, Jeyamary; Fritsch, Peter W.; Mohanan, Narayanan Nair; Liriina, Daihrii Kaikho (Phytotaxa, 2021)
In a comprehensive taxonomic revision of the Old World species of Symplocos (Symplocaceae) many infraspecific taxa were recognized within S. macrophylla, but subsequently most of these have been either moved to other species or recognized at the species rank. Following this trend, we provide herewith morphological evidence to warrant the elevation of S. macrophylla subsp. namboodiriana to the species rank. Symplocos namboodiriana comb. & stat. nov. differs from the other subspecies of S. macrophylla in its 1-flowered inflorescences (versus multi-flowered), shorter bracts, and 4 to 6 secondary leaf veins (versus longer bracts and 6 to 13 secondary veins). We provide an updated description of the species along with photographic images of live specimens and a conservation threat assessment.